Fracture Limits of Maxillary Fourth Premolar Teeth in Domestic Dogs Under Applied Forces - Soltero-Rivera, Maria; Elliott, Matthew I.; Hast, Michael W.; Shetye, Snehal S.; Castejon-Gonzalez, Ana C.; Villamizar-Martinez, Lenin A.; Stefanovski, Darko; Reiter, Alexander M. (Frontiers in Veterinary Science, 2019)
A cadaveric study was performed to investigate the external mechanical forces required to fracture maxillary fourth premolar teeth in domestic dogs and describe a clinically relevant model of chewing forces placed on functionally important teeth in which fracture patterns are consistent with those defined by the American Veterinary Dental College (AVDC). Twenty-four maxillary fourth premolar teeth harvested from dog cadavers. Samples consisted of maxillary fourth premolar teeth with surrounding alveolar bone potted in polycarbonate cylinders filled with acrylic. The cylinders were held by an aluminum device at an angle of 60° with respect to the ground. An axial compression test was performed, creating a force upon the occluso-palatal aspects of the main cusps of the crowns of the teeth. The highest compressive force prior to failure was considered the maximum force sustained by the teeth. Results showed the mean maximum force (± SD) sustained by the tested teeth at the point of fracture was 1,281 N (± 403 N) at a mean impact angle (± SD) of 59.7° (± 5.2°). The most common fracture type that occurred among all samples was a complicated crown fracture (n=12), followed by an uncomplicated crown fracture (n=6), complicated crown-root fracture (n=5), and uncomplicated crown-root fracture (n=1). There was no statistically significant correlation between dog breed, age, weight, impact angle, crown height or crown diameter and the maximum force applied at the point of fracture. The only independent variable that remained significantly associated with maximum force was the crown height to diameter ratio (p=0.005), suggesting that a decreased ratio increases tooth fracture resistance. The methodology described herein has been successful in creating a pattern of fracture of maxillary fourth premolar teeth consistent with that defined by the AVDC under angled compression at forces within the maximum chewing capability of the average domestic dog.